Facile synthesis of Ag NPs@ MIL-100(Fe)/ guar gum hybrid hydrogel as a versatile photocatalyst for wastewater remediation: Photocatalytic degradation, water/oil separation and bacterial inactivation. (15th February 2020) - Duan, Chao; Liu, Chaoran; Meng, Xin; Gao, Kun; Lu, Wanli; Zhang, Yanling; Dai, Lei; Zhao, Wei; Xiong, Chuanyin; Wang, Wenliang; Liu, Yishan; Ni, Yonghao
Graphical abstract: Highlights: 3D bio-based hybrid hydrogel of Ag NPs@MIL-100(Fe)/ GG was fabricated. The hybrid hydrogel can be used for sophisticated wastewater remediation. Ag NPs in the hydrogel enhanced both the photocatalytic and antibacterial activity. A high photocatalytic degradation of dyes due to the synergistic adsorption and photocatalysis. Efficient separation of oily wastewater and anti-bacteria property in the hydrogel. Abstract: 3D Hydrogel is one of the most popular adsorbents for water remediation due to its excellent concentration/ adsorption capacity. However, it remains a challenge to use the hydrogel alone for treating complex wastewater. In this work, we designed and fabricated a versatile bio-based hybrid hydrogel consisting of Ag NPs@ MIL-100(Fe) photocatalysts and guar gum (GG) via facile blending and self-crosslinking. The hybrid hydrogel integrated with multifunctions of dye adsorption and degradation, oil/water separation and antibacterial properties, thus enabling its applications in complex wastewater remediation process. The presence of Ag nanoparticles (Ag NPs) not only enhanced the photocatalytic activity of MIL-100(Fe), but also imparted the antibacterial activity of Ag NPs@MIL-100(Fe)/ GG hydrogel. Particularly, the bio-based GG hydrogel scaffold showed excellent injectable, remodeling, and self-healing properties, which enabled an effective oil/water separation ability (silicone oil, cyclohexane and canola oil) and facilitated the recyclability/sustainability of the nano-photocatalyst powders. This novel multifunctional 3D hybrid hydrogel provides new opportunities for wastewater remediation purpose.